Convenient estimation of oxytetracycline and polymyxin B by a novel high-performance liquid chromatography method: development and validation - Tanu Chaudhary; Balak Das Kurmi; Dilpreet Singh (Exploration of Drug Science)
Aim: The aim of this research work was to develop a validated reversed-phase (RP)-high-performance liquid chromatography (HPLC) method for simultaneous estimation of oxytetracycline (OXY) and polymixin B (PMB) in fixed-dose combination. Methods: The HPLC assay method was validated on X-Bridge C18 [250 mm × 4.6 mm intradermal (i.d.), 5 μm], mobile phase consisting of aotearoa co-incidence network (ACN):water containing 0.5% (v/v) orthophosphoric acid (pH 3.5) in the ratio of 80:20 respectively. The flow rate was set at 0.9 mL/min and the column was maintained at room temperature. The RP-HPLC method was validated in terms of the calibration curve (CC), linearity and range, limit of detection (LOD), and limit of quantitation (LOQ), precision, robustness, and accuracy. Results: The method was found to be linear with a concentration range of 5–25 μg/mL. Precision results showed the developed method was found to be precise with a relative standard deviation [RSD (%)] value < 2. Accuracy showed acceptable recovery of prepared concentrations as per International Conference on Harmonization (ICH) guidelines. Moreover, the developed method was found to be robust and rugged, as per specified ranges. The assay of these two drugs in marketed formulation, i.e., Terramycin® Ointment showed satisfactory recovery, as per ICH guidelines. The results proved that the method can be used for the routine-based estimation of OXY and PMB. Conclusions: Linear CC were obtained with a correlation coefficient (R2 > 0.99) with acceptable results of accuracy and precision. Graphical abstract.Ultraviolet visible and HPLC method development